Mechanisms of immune evasion utilised by the Hepatitis C virus - Petrovic, Danijela (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2009)
Hepatitis C virus (HCV) is a small, enveloped RNA virus which is distributed worldwide and according to the WHO the number of infected individuals is estimated to be approximately 170 million. HCV creates a heavy burden on a public health, since most HCV infections persist, leading in up to 80% of all cases to chronic hepatitis associated with liver fibrosis, cirrhosis and hepatocellular carcinoma. A successful immune response to HCV is characterised by a vigorous, sustained and multi-specific cellular response during the acute phase of infection. However, the persistence of HCV in infected individuals, is due mainly to its ability to evade immune defense, which it does using complex strategies to establish persistence and chronic disease.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin